Dakwah Inklusif -Inovatif Masyarakat Tradisi Nyadran Di Desa Talang Rejoso Nganjuk: Analisis Bimbingan Konseling Islam, Menyempurnakan Spiritual Umat (Jurnal Bimbingan dan Konseling Islam, 2019)
This article examines the phenomenon of inclusive da’wah within the Nyadran tradition in Nganjuk, East Java. The question is how can preachers can properly guide and counsel the Islamic community without clashing with the Nyadran ritual which incidentally is based on Hindu-Buddhist teachings? This study uses a qualitative-descriptive method to explain the data in the form of a da’wah counseling model carried out by preachers in teaching Islam in the Nyadran community. Data collection used observation and in-dept interviews with religious leaders, traditional leaders, and 5 community representatives. Data analysis uses critical-synthetic thinking methods. The result is; First, Nyadran is a ritual of giving offerings (sesajen) to an ancestor, Punden Mbah Raden, in order to protect people’s lives. The da’i modify the offerings into a ‘Tumpengan’ ritual which is taken to the mosque or village hall for Dzikir Tahlil, Yasinan, and Istighosah. Tumpeng is eaten together after dzikir, and the rest is divided to be taken home as a ‘berkat’. Second, the preachers provide guidance, both individually or in group, that is: Nyadran is good because it represents an attitude of gratitude to the ancestors; Food offerings for Punden are worthless, so it must be used for those who are still alive. Third, thanking Punden with offerings is constructed into an Earth Alm ritual, namely sharing sustenance from crops, followed by cleaning the village yard and a competition to decorate the environtment.